Antiviral Activity of Synthetic Aminopyrrolic Carbohydrate Binding Agents: Targeting the Glycans of Viral gp120 to Inhibit HIV Entry. Issue 28 (1st June 2015) - Francesconi, Oscar; Nativi, Cristina; Gabrielli, Gabriele; De Simone, Irene; Noppen, Sam; Balzarini, Jan; Liekens, Sandra; Roelens, Stefano
Abstract The binding abilities of a set of structurally related aminopyrrolic synthetic receptors for mannosides, endowed with antimycotic activity against yeast and yeast‐like pathogens bearing mannoproteins on their cell surface, have been investigated towards the highly mannosylated gp120 and gp41 glycoproteins of the HIV envelope. A pronounced binding interaction with both glycoproteins was observed by SPR for most of the investigated compounds. Comparison of their binding properties towards the glycoproteins with their binding affinities toward mannosides revealed a direct correlation, supporting their role as carbohydrate binding agents (CBAs). Cytostatic activity studies revealed antiproliferative activity dependent on the nature and the structure of compounds. Antiviral activity studies against a broad panel of DNA and RNA viruses showed inhibitory effect against HIV infection of the T‐lymphocyte CEM cell line for two compounds, suggesting antiviral activity similar to other CBAs, such as the nonpeptidic pradimicin antibiotics.